Development of Interactive Multimedia for Human Reproduction System in Junior High School - Puspitasari, Dina Nafisa; Indriyanti, Dyah Rini; WH, Nugrahaningsih (Journal of Biology Education, 2019)
The study was aim to find out the effectiveness of the multimedia interactive for human reproduction system learning. The research was done at Junior High School 5 Pemalang with the design of research is Research and Development (R&D). The small scale trial of the product was done in 23 students with proportionate stratified random sampling method. The larger scale trial of the product was done in IX A class with Purposive Sampling Method and One Group Pre-test Post-test Experimental Design. The assessment from the experts to the multimedia interactive for system human reproduction learning obtains a high score as much as 89.58% for course assessment and 97.22% for media assessment. The results from the teacher and students response questionnaire in small scale trial obtain the average percentage as much as 100 % and 81.55 % respectively, which was high qualified. The effectiveness of Multimedia Interactive in learning could be seen in pretest and post test results with calculating N-gain and obtain N-gain 0.54, which was categorized as middle. Beside N-gain, the completeness of understanding the concepts become another effectiveness of multimedia interactive obtain 88% in classical completeness. The results of the study shows that the multimedia interactive was qualified and effective to enhance the students’ learning outcome in the course of system human reproduction.